Business models and sustainability: opportunities and challenges perceived by micro and small Brazilian companies. (27th April 2023) - Stocco, Lucas Conde; Granjeiro, Paulo Afonso
This article aims to identify opportunities and challenges of innovation for sustainability perceived by micro and small enterprises (MSEs) for developing new business models. Questionnaires were applied to companies participating in the local innovation agent (agente local de inovação - ALI) Program in a Brazilian city to survey their perceptions and management practices concerning sustainability and innovation that allow the development of new business models, with 13 responses being obtained. Descriptive statistics analysed the data. The results show that innovation for sustainability generates opportunities such as new businesses, strengthening the supplier network, winning over new customers and generating better results. The study also highlighted challenges in business model innovation for sustainability, such as: finding suppliers and partners for sustainable inputs that practice sustainability, information and incentives from the public authorities, customer culture for acquiring sustainable products and services and lack of financial resources to invest in innovation were found.